2020
DOI: 10.1080/10615806.2020.1795139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of waiting patiently as coping strategy for an interpersonal stressor on depressive symptoms

Abstract: Background: Coping behavior is known to moderate the effect of stressors on depressive symptoms. Increased reassessing coping, that is, waiting patiently for an appropriate opportunity to handle a stressful relationship, as coping strategy for interpersonal stressors is associated with lower depressive symptoms. Objectives: We hypothesized that higher reassessing coping would be associated with lower depressive symptoms in individuals with higher coping flexibility. Coping flexibility is the ability to discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The PHQ-9 has been used to treat depressive symptoms in individuals and patients with chronic pain [ 17 , 22 , 24 , 26 , 30 ]. The Japanese version is strongly correlated with another scale designed to measure depressive symptoms [ 44 ]. Additionally, the Cronbach’s alphas for the Japanese version were 0.83 for a relatively large sample of college students ( n = 1468) [ 44 ] and 0.82 for the sample with chronic pain [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PHQ-9 has been used to treat depressive symptoms in individuals and patients with chronic pain [ 17 , 22 , 24 , 26 , 30 ]. The Japanese version is strongly correlated with another scale designed to measure depressive symptoms [ 44 ]. Additionally, the Cronbach’s alphas for the Japanese version were 0.83 for a relatively large sample of college students ( n = 1468) [ 44 ] and 0.82 for the sample with chronic pain [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Japanese version is strongly correlated with another scale designed to measure depressive symptoms [ 44 ]. Additionally, the Cronbach’s alphas for the Japanese version were 0.83 for a relatively large sample of college students ( n = 1468) [ 44 ] and 0.82 for the sample with chronic pain [ 18 ]. In this study, participants rated the degree to which they had experienced each item during the past two weeks on a four-point Likert scale (0 = not at all to 3 = nearly every day ).…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, poor coping flexibility refers to the perseveration of failed coping strategies, leading to hopelessness and depression (Nummenmaa & Niemi, 2004;Sheppes et al, 2015). Indeed, based on the dual-process theory, poor coping flexibility predicts increased depressive symptoms (e.g., Kato, 2012Kato, , 2015bKato, , 2015cKato, , 2015dKato, , 2016aKato, , 2017Kato, , 2020aKato, , 2020bDang et al, 2019;Kato et al, 2019;Southward & Cheavens, 2017;Wan Mohd Yunus et al, 2019). Additionally, it can be assumed that poor coping flexibility may predict suicidal risk.…”
mentioning
confidence: 99%
“…The coping flexibility hypothesis [ 10 ] posits that greater coping flexibility will produce more adaptive outcomes in psychological and physical responses to stressors [ 14 , 15 ]. This hypothesis, which is based on the principles of the dual-process theory, has been supported through studies done in multiple countries, such as the United States [ 17 , 18 , 19 , 20 , 21 ], the United Kingdom [ 22 ], Poland [ 23 , 24 ], Australia [ 19 ], Canada [ 25 ], China [ 19 , 26 , 27 ], Hong Kong [ 28 , 29 ], Japan [ 10 , 11 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], India [ 20 , 37 ], Malaysia [ 38 ], and Israel [ 39 , 40 ]. For example, greater coping flexibility was found to be associated with lower change scores from baseline to reactivity in heart rate and systolic blood pressure responses during a stressful cognitive task, but not during a non-stressful task [ 33 ], indicating that greater coping flexibility reduces cardiovascular reactivity to a stressful task.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a principal response to chronic stress [ 41 , 42 ]. Many studies have demonstrated that lower coping flexibility based on the dual-process theory is associated with lower levels of depression [ 10 , 17 , 19 , 21 , 23 , 26 , 27 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. For example, both abandonment and re-coping were found to explain a unique amount of the variance in depressive symptoms after 14 weeks from baseline, beyond coping flexibility as measured by other approaches (i.e., coping repertoire, coping variability, and coping fitness) as well as typical coping strategies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%